Respostas

2014-04-16T22:14:37-03:00
A) 9x² + 3x + 1 = 4x²
9x² + 3x -4x² + 1 =0
5x² -4x + 1 =0

a=5  b= -4  c=1

Δ=b² - 4.a.c
Δ=(-4)² -4.5.1
Δ=16 -20
Δ=-4
Não existe Δ negativo,então S={ }


b)9x² - 1 =3x -3
9x² - 3x -1 +3 =0
9x² -3x +2 =0

a=9  b= -3  c= 2


Δ=b² -4.a.c
Δ=(-3)² - 4 .9.2
Δ=9 - 72
Δ=63




c)6(x² - 1)- 14 =5x² + x
6x² - 6 -14 -5x² - x =0
x² - x -20 =0
a=1  b= -1  c= -20

Δ=b² - 4.a.c
Δ=(-1)² -4.1.(-20)
Δ=1 +80
Δ=81

X= -b +- √Δ
         2.a

x= - (- 1 ) +- √81
           2.1

x= 1 +- 9
        2

x' = 1 - 9    = -8   = - 4 
         2          2

x'' = 1 + 9 = 10 = 5       S ={ -4 , 5 }
           2       2